Cover Feature: Controlled Synthesis of Hollow PbS‐TiO2 Hybrid Structures through an Ion Adsorption–Heating Process and their Photocatalytic Activity (Chem. Asian J. 22/2017). Issue 22 (25th October 2017) - Xia, Hongbo; Wu, Suli; Zhang, Shufen
Abstract : Hollow hybrid structures : Combining Ostwald ripening effect and Kirkendall effect is an attractive strategy to fabricate hollow structures. In this work, a synthetic strategy of hollow hybrid structures comprising two semiconductors has been developed. Monodisperse TiO2  spheres functionalized by sulfhydryl (SH) groups were used as substrates. Thus, metal ions can be adsorbed by ‐SH groups to form metal thiolates, and the C−S bonds can dissociate by heating to release S 2− . Meanwhile, the amorphous TiO2 spheres were transformed into anatase phase during the reaction. As a result, a monodisperse hybrid hollow structure that exhibited enhanced photocatalytic activity could be obtained. More information can be found in the Full Paper by Suli Wu et al. onpage 2942 in Issue 22, 2017 (DOI:10.1002/asia.201701204 ).